Cerebrospinal Fluid Rhinorrhea: Causes, Sites, Management and Recurrence - Khalid B. Al-Ghamdi; Almoaidbellah A. Rammal; Rafat S. Sindi (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to report the sites, management and recurrence of rhinorrhea, and to compare our results with those obtained from other centers. The medical records of patients with cerebrospinal fluid rhinorrhea in Otorhinolaryngology, and Head and Neck Surgery Department at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, from January 2003 to May 2011 were retrospectively reviewed. Ten cases of cerebrospinal fluid rhinorrhea were treated during the study period. The most frequent causes were endoscopic sinus surgery (50%), spontaneous (30%) and others (20%). Defects were located at the cerebriform plate (n = 6), left fronto-ethmoidal area (n = 1), at roof of the left frontal sinus (n = 1), at the junction between the cerebriform plate and bulla ethmoidalis (n = 1), and at the roof of the sphenoid sinus (n = 1). Patients were followed up for 6 to 24 months. The initial closure was successful in 6 patients; 5 after endoscopic sinus surgery and 1 after conservative treatment. Overall closure rate was 90.0%; 87.5% after endoscopic sinus surgeries. In conclusion, the most frequent cause of cerebrospinal fluid rhinorrhea was endoscopic sinus surgery and the cerebriform plate was the most common defect location. The overall rate of closure after endoscopic sinus surgery and conservative treatment was high.